Efeito da associação de laserterapia e própolis na cicatrização de feridas em ratos diabéticos - Barreto, Mardem Portela e Vasconcelos (2017)
Diabetes mellitus causes a number of systemic complications, including delay in the healing process. Several therapeutic alternatives have been tested in in vitro and in vivo studies in order to promote improvement in the process of wound repair in diabetic animals and individuals. The aim of the present study was to evaluate the effect of the association of low intensity laser therapy and topical administration of green propolis in cutaneous wounds model in rats with streptozotocin-induced diabetes. Ninety animals were allocated in the following groups: (N) normoglycemic (not induced), without therapy; (C) diabetic control, without therapy; (L) undergoing low intensity laser therapy (660 nm, 30 mW, 4 J/cm2); (P) submitted to topical administration of green propolis (30% alcoholic extract); and (LP) submitted to the combination of laser therapy and topical administration of green propolis. Therapeutic procedures were performed every 24 hours for 6 days. The surgical areas were photographed to evaluate the wound closure area. At intervals of 7, 14 and 21 days, the animals were submitted to euthanasia and subsequent removal of the wound area. The specimens were fixed, routinely processed, and embedded in paraffin and the slides obtained were stained by H/E and Picrosirius red for evaluation of re-epithelization, intensity of inflammatory infiltrate, and formation and organization of collagen, and also submitted to immunostaining for FGF-2 and VEGF. The quantitative data were submitted to non-parametric statistical tests, with a 95% confidence interval. The macroscopic evaluation of the wound area showed that the three groups submitted to treatment (L, P, and LP) showed an acceleration of wound retraction in relation to group C (p <0.001) from the 3rd to the 14th day, with results similar to group N. The LP group presented a better result in relation to the others (p <0.05) from the 5th day onwards. Histological analysis showed that the treated groups exhibited higher rates of re-epithelialization, especially in the L and LP groups, as well as lower inflammation rates, especially in the LP and P groups. Regarding the collagen I/III ratio, it was observed on the 7th day higher values in the LP group compared to the C group (p <0.05), similar to the N group. On the 14th day, the L group presented the highest proportion of the treated groups, resembling to the results of group N and with statistical difference for the other experimental groups (p <0.01). There was no difference in the collagen I/III ratio among the groups at the 21-day interval. The three treated groups (L, P, and LP) exhibited lower expression of FGF-2 and VEGF compared to N and C groups, especially the LP group (p <0.05). Taken together, the results of the present study allow us to conclude that the association of laser therapy with the topical application of propolis improves the cutaneous wound repair in the animal model of diabetes studied.